Effects of gibberellic acid and N, N-dimethyl piperidinium chloride on the dose of and physiological responses to prometryn in black nightshade (Solanum nigrum L.). - Hailan Jiang; Xiaoxia Deng; Jungang Wang; Jing Wang; Jun Peng; Tingting Zhou (PLoS ONE, 2014)
The use of gibberellic acid (GA3) and N, N-dimethyl piperidinium chloride (DPC) in combination with prometryn would likely increase the control of black nightshade in cotton fields. Experiments were designed to investigate the physiological and biochemical responses of black nightshade at the three- to four-leaf stage to prometryn applied at different rates, either alone or in combination with GA3 or DPC, in a greenhouse environment. These studies demonstrated that prometryn applied in combination with DPC at low rates (7.2 g ai ha(-1)) led to increased fresh weight and visible injury of black nightshade compared with prometryn applied alone or in combination with GA3; however, at rates of 36, 180, and 900 g ai ha(-1), prometryn in combination with DPC caused the least visible injury among all treatments and prometryn in combination with GA3 caused the greatest visible injury. These results suggest that black nightshade suffered more severe damage when prometryn was applied in combination with GA3, which is supported by the reduced soluble protein content, lower antioxidant enzyme activities, and higher malondialdehyde (MDA) content in the plants treated with prometryn plus GA3. These results indicate that the application of GA3 in combination with prometryn to black nightshade may have the potential to lower the levels of prometryn tolerance in these plants.